Managing Newspaper Clippings in Print Media Libraries: A Study - Kumar, Parveen; Mahajan, Preeti (Journal of Information and Knowledge, 2018)
This study is about the management of newspaper clippings in print media libraries of North India. The study includes data from twelve print media libraries from north India. The data was collected using the questionnaire method. The result shows that the print media libraries used traditional methods for storing newspaper clippings. Only 16.66% of the newspaper libraries used computerized indexing for managing their newspaper collection.